PARENT-CHILD CHARACTERISTICS AND ITS CORRELATION TO PARENTAL REJECTION OF AUTISM SPECTRUM DISORDERS CHILDREN - Sahida, Khaula; Allenidekania, . (LIFE: International Journal of Health and Life-Sciences, 2018)
The presence of autism spectrum disorders (ASD) children in the family affect the parental acceptance and rejection of a child's condition which involves a psychological response at every process. This study aims to determine the correlation between parent and children characteristics with parental rejection level of children with ASD. Cross-sectional analytic was performed in this study. The variable was categorical and numerical. The participant of this study were sixty one parents of ASD children in South Jakarta that recruited by cluster random sampling. This study used parental acceptance-rejection questionnaire which adapted from Parent Acceptance-Rejection Questionnaire (PARQ) and modified by researcher. Bivariate analysis showed that there was no significant correlation between parent gender (p=-0145; r=0,264), parent age (p=-0,104; r=0,425), parent ethnic (p=-0,123; r=0,345), parent religion (p=-0,072; r=0,345), parent occupation (p=0,138; r=0,285), parent income (p=0,010; r=0,938), amount of children (p=-0,121; r=0,353), and child gender (p=-0,088; r=0,499) with parental rejection of ASD child. In contrast, there was a significant correlation between parent education level (p=0,008; r=-0,337) and child age (p=0,020; r=-0,296) with the levels of parental rejection. In conclusion, only parents educational background and child age which affects to parental rejection of ASD child condition. This result showed that it is quite important to all nurses for giving more attention to factors that may relate to parental acceptance which can be affecting to child care.